Copolymerization of benzyl methacrylate and a methacrylate bearing benzophenoxy and hydroxyl side groups: Monomer reactivity ratios, thermal studies and dielectric measurements - Biryan, Fatih; Demirelli, Kadir (Korean Fiber Soc, 2017)
Statistical copolymers of 2-hydroxy-3-benzophenoxy propyl methacrylate (HBPPMA) and benzyl methacrylate (BzMA) in different feed ratios were synthesized by free radical copolymerization method at 60 A degrees C in presence of AIBN initiator. The compositions of copolymer were estimated from H-1-NMR technique. The monomer reactivity ratios of HBPPMA and BzMA were calculated as r(1) (r(HBPPMA))=0.51 +/- 0.076 and r(2) (r(BzMA))=1.07 +/- 0.140 for Kelen-Tudos method, and was estimated as r(1)=0.37 +/- 0.0006 and r(2)=0.64 +/- 0.0485 according to Fineman Ross equation. The average values estimated from the two methods showed that monomer reactivity ratio of benzyl methacrylate was a slightly high in comparison to HBPPMA. The copolymer system showed an azeotropic point, which is equal to M (BzMA) =m (BzMA) =0.43. DSC measurements showed that the T-g's of poly(HBPPMA) and poly(BzMA) were 84 A degrees C and 73 A degrees C, respectively. The T-g in the copolymer system decreased with increase in benzyl methacrylate content. The decomposition temperature of poly(BzMA) and poly(HBPPMA) occurs in a single stage at about 207 A degrees C and 260 A degrees C, respectively. Those of HBPPMA-BzMA copolymer systems are between decomposition temperatures of two homopolymers. The dielectric constant, dielectric loss factor and electrical conductivity were investigated depend on the frequency of the copolymers. The highest dielectric constants depending on all the studied frequencies were recorded for the poly(HBPPMA) and the copolymer containing the highest HBPPMA unit. The dielectric constant for P(HBPPMA) and P(BzMA) at 1 kHz are 6.56 and 3.22, respectively. Also, those of copolymer systems were estimated between these two values. Similarly, poly(HBPPMA) and copolymers, which are prepared under the same conditions show the dissipation factor and conductivity as well.
Keywords: Copolymerization; Monomer reactivity ratios; Thermal studies; Dielectric behaviors; Poly(benzyl methacrylate)